2014
DOI: 10.1007/s10620-014-3086-6
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Pilot Study: Effects of an Exercise Programme and Leucine Supplementation in Patients with Cirrhosis

Abstract: A programme of moderate physical exercise together with leucine supplements in patients with cirrhosis is safe and improves exercise capacity, leg muscle mass and HRQoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
166
2
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(194 citation statements)
references
References 51 publications
8
166
2
2
Order By: Relevance
“…However, 2 metaanalyses have suggested that supplemental nutrition does not improve nutritional our clinical outcomes[22,23]. This is because patients with liver disease are believed to be in a state of anabolic resistance that prevents appropriate skeletal muscle responses to nutrient administration[37]. Skeletal muscle mass is maintained by a balance between protein synthesis, breakdown and possibly the regenerative potential mediated by the myogenically committed stem cells, satellite cells[1].…”
Section: Mechanisms Of Sarcopenia In Cirrhosismentioning
confidence: 99%
See 1 more Smart Citation
“…However, 2 metaanalyses have suggested that supplemental nutrition does not improve nutritional our clinical outcomes[22,23]. This is because patients with liver disease are believed to be in a state of anabolic resistance that prevents appropriate skeletal muscle responses to nutrient administration[37]. Skeletal muscle mass is maintained by a balance between protein synthesis, breakdown and possibly the regenerative potential mediated by the myogenically committed stem cells, satellite cells[1].…”
Section: Mechanisms Of Sarcopenia In Cirrhosismentioning
confidence: 99%
“…To overcome anabolic resistance, a strategy that has been beneficial is to shorten the postabsorptive or fasting state. Overnight fasting provides the greatest window of anabolic opportunity but frequent overnight feeding is difficult, causes sleep disturbances and has the potential for aggravating both reflux and insulin resistance[37]. To overcome these limitations by avoiding fasting induced proteolysis and lipolysis, frequent feeding and late evening snacks have been used with some benefit.…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…62 A pilot study revealed improvement in a 6-minute walk test in those who combined daily leucine supplementations with hour-long treadmill and cycle exercise 3 times a week with to achieve 60% to 70% maximum heart rate. 89 In this randomized pilot study, 17 patients with cirrhosis were randomized to a treatment arm consisting of 12 weeks of exercise, or control. At the 24-week follow-up, patients who exercised had a significant increase in thigh muscle circumference and in overall weight.…”
Section: Management Of Frailty and Sarcopenia In Patients With Cirrhomentioning
confidence: 99%
“…The intervention group had improvement in 2-min step test, increased thigh circumference, and improved quality of life compared to no interval change in the control group. No adverse events were seen in the intervention group [70]. Additionally, several studies have demonstrated that formalized exercise regimen will improve insulin sensitivity among patients with liver disease, which is particularly important among patients with sarcopenic obesity [71][72][73].…”
Section: Exercise and Preservation Of Muscle Massmentioning
confidence: 86%